Evaluation of Project-Based Assessment in Improving Critical Thinking Skills of Middle School Students - Aras, Muhamad (Journal of Pedagogi, 2025)
This study aims to in-depth evaluate the implementation of project-based assessment in improving the critical thinking skills of secondary school students. The main focus of this study is to examine how this approach is implemented in the learning process and its impact on students' higher-order thinking skills. The method used is a descriptive qualitative approach with data collection techniques such as participatory observation, in-depth interviews with teachers and students, and analysis of learning project documentation. The research subjects included teachers and students who were actively involved in project-based learning activities in a secondary school. The results show that project-based assessment contributes positively to increasing student participation and strengthening critical thinking skills, especially in the aspects of analysis, evaluation, interpretation, and problem-solving. Students demonstrated higher cognitive engagement, were able to work collaboratively in developing solutions to real-life problems, and reflected more deeply on their learning processes and outcomes. Furthermore, teachers assessed this approach as providing a more comprehensive picture of learning compared to conventional assessment methods. However, the implementation of project assessment still faces several obstacles, such as limited learning time, gaps in teachers' understanding of authentic assessment, and differences in student abilities. Based on these findings, the study recommends the need for intensive training for teachers on planning and implementing project-based assessments, as well as school policy support that accommodates the allocation of time, resources, and technical guidance to ensure the sustainability and effectiveness of this approach in the context of 21st-century learning.